Injil Barnabas Dan Makna Pentingnya Dalam Studi Heresiologi - Yosef Yunandow Siahaan (Jurnal Teologi dan Pelayanan Kerusso, 2021)
The Portrait of Jesus in the Apocryphal Gospels often contradicts the Portrait of Jesus in the Canonical Gospels in the New Testament. For evangelical-orthodox Christianity, the canon of the Scriptures has been final, and has been endorsed at the Hippo and Carthage councils, however some Muslims always make the news that the Apocryphal Gospels, especially the Gospel of Barnabas, are the original Gospels, while the gospels accepted by Christians today is a false gospel. This interest is worth examining aside, looking into the texts of the Gospel of Barnabas insofar as they pertain to Biblical Teaching. This study will use a biblical approach to library research. Namely by looking at the texts in the Gospel of Barnabas and comparing them with the Bible text of the New Testament by doing a little exposition of some parts of the Bible. After all, the Bible is the primary source because it comes from direct eye witnesses and is only fifteen to sixty years apart from the time Jesus lived. The problem is that the Gospel of Barnabas has been mentioned in the Pseudo Gelasius I Decree which seems to support that the Gospel of Barnabas was written by the Apostle Barnabas during his lifetime. However, it is easy to trace that the Gospel of Barnabas contains many trivial errors that could not have been written by the Apostle Barnabas who had a Jewish background, living in the Palestinian-Israel area in the first century AD. Doing a study of the time of writing, writers, geographic and religious background, and language, if necessary the theological motive needs to be done in order to study the study of Heresiology or teachings that deviate from the truth of Evangelical-Orthodox Christianity. Abstrak Indonesia Potret Yesus dalam Injil-Injil Apokrif seringkali bertolak belakang dengan Potret Yesus dalam Injil-Injl Kanonik yang ada dalam Alkitab Perjanjian Baru. Bagi kekristenan yang Injili-ortodoks kanon Kitab suci telah bersifat final, dan telah disahkan pada konsili Hippo dan Kartago, Namun sebagian umat Islam selalu membuat berita bahwa Injil-injil Apokrif khususnya Injil Barnabas adalah Injil yang asli, sedangkan injil yang diterima orang Kristen saat ini adalah Injil yang palsu. Minat tersebut layak dikaji di samping, melihat ke dalam teks-teks Injil Barnabas sejauh itu bersinggungan dengan Ajaran Alkitab. Penelitian ini akan menggunakan pendekatan penelitian kepustakaan yang bersifat biblika. Yaitu dengan melihat teks-teks dalam Injil Barnabas dan membandingkan dengan teks Alkitab Perjanjian Baru dengan melakukan sedikit eksposisi dari beberapa bagian Alkitab. Bagaimanapun juga Alkitab adalah sumber primer karena berasal dari saksi mata langsung dan hanya berjarak lima belas hingga enam puluh tahun sejak Yesus hidup. Masalahnya Injil Barnabas pernah di sebut dalam Dekrit Pseudo Gelasius I yang tampaknya mendukung bahwa Injil Barnabas di tulis oleh Rasul Barnabas semasa hidupnya. Namun mudah saja di lacak bahwa Injil Barnabas mengandung banyak kesalahan-kesalahan sepele yang tidak mungkin di tulis oleh Rasul Barnabas yang berlatar belakang Yahudi, tinggal di daerah Palestina-Israel pada abad pertama Masehi. Melakukan kajian terhadap waktu penulisan, penulis, latar belakang geografi dan keagamaan, dan Bahasa, jika diperlukan motif teologisnya perlu dilakukan dalam rangka mempelajari studi Heresiologi atau ajaran-ajaran menyimpang dari kebenaran Injili-Ortodoks kekristenan.